Effects of salinity on lipids reserves, survival and growth of flathead grey mullet Mugil cephalus (Linnaeus, 1758). (24th August 2022) - Loi, Barbara; Leggieri, Francesca; Giménez Papiol, Gemma; Carta, Gianfranca; Banni, Sebastiano; Carboni, Stefano; Vallainc, Dario
Abstract: Salinity is one of the main factors affecting physiological performances of teleost fish. Its influence on survival and growth rate of juvenile (five months old) Mugil cephalus (25.33 ± 1.01 mm length) was tested under hatchery conditions. After acclimation, fish were reared for three months at two salinities: freshwater (FW, 0 ppt) and saltwater (SW, 36 ppt). At the end of the experiment, growth, survival, and lipids deposition in the liver and carcasses were evaluated by histological and biochemical methods. Survival was high and similar between treatments. Fish reared in SW showed a significantly higher specific growth rate for body weight while Condition Index was similar. Lipid accumulation in the liver and total lipids and fatty acid profiles in the whole body were also similar among salinity treatments, while the levels of bioactive metabolite N‐acylethanolamines were significantly higher in fish reared in FW. The high survival rate, a similar Condition Index and lipid deposition in both treatments strongly suggest that the transfer of mullet juveniles from SW hatchery conditions to FW is a viable commercial scale production strategy. These results contribute to our understanding of mullet juveniles' performances under different salinities and indicate that FW conditions provide a suitable environment for mullet juveniles.